2017
DOI: 10.1002/cnma.201700062
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Gold‐Loaded Fluorinated Titania Inverse Opal Photocatalysts for Enhanced Solar‐Light‐Driven Hydrogen Production

Abstract: This work reports the preparation of in situ gold‐loaded fluorinated titania inverse opal (Au/F TiO2 IO) photocatalysts for enhancing solar‐light‐driven hydrogen evolution. The use of trifluoroacetic acid facilitates the surface fluorination as well as the in situ deposition of gold nanoparticles (AuNPs) at the defect sites on the TiO2 surface. The thermal treatment partially fuses the gold and titania nanoparticles leading to enhanced hot electron injection when illuminated under solar light. Au/F TiO2 IO‐215… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…The proper selection of the type of titania nanostructure together with considering the heterostructure engineering (e.g., coupling) or titania modification is the complex strategy to design the photocatalytic materials, which are oriented for the specific reaction systems. Despite the wide discussion about the mechanisms and reasons responsible for the specific properties of different photocatalysts, solar cells, energy storage, [158][159][160][161], [163,164], [168][169][170], [202][203][204] In the discussion of 1D and 3D nanostructures, the exceptional role of photonic nanocrystals in the form of titania nanotubes and 3D structures has been shown. The exceptional property of IO-PCs is the possibility of PBG tuning.…”
Section: Discussionmentioning
confidence: 99%
“…The proper selection of the type of titania nanostructure together with considering the heterostructure engineering (e.g., coupling) or titania modification is the complex strategy to design the photocatalytic materials, which are oriented for the specific reaction systems. Despite the wide discussion about the mechanisms and reasons responsible for the specific properties of different photocatalysts, solar cells, energy storage, [158][159][160][161], [163,164], [168][169][170], [202][203][204] In the discussion of 1D and 3D nanostructures, the exceptional role of photonic nanocrystals in the form of titania nanotubes and 3D structures has been shown. The exceptional property of IO-PCs is the possibility of PBG tuning.…”
Section: Discussionmentioning
confidence: 99%
“…A very fast rate for the hydrogen production reaction was observed for the Au−Pt nanoparticle loaded, N−F co‐doped titania inverse opals under simulated solar light irradiation due to the synergism between chemical, photonic and plasmonic effects. We noted that the inverse opal photocatalysts described in this work exhibited much higher hydrogen evolution rate compared to most of the recent reports related to hydrogen production experiments with inverse opaline materials …”
Section: Introductionmentioning
confidence: 41%
“…In addition to these chemical effects; the physical effects originated from the inverse opaline structure has a significant role in enhancing the hydrogen evolution profile of the photocatalysts. We have recently investigated and reported the effects of non‐metallic doping/ self‐doping (F or Ti 3+ ) and the in situ loading of Au or Au and Pt co‐catalyst systems on hydrogen production profiles of the TiO 2 photocatalysts ,. The results from these studies are compared with the results from the current work and listed in the Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the slow photon effect and multiple scattering effect can promote the optical path, thus increasing the light absorption and further enhancing the light–matter interactions. [ 108,109 ] Therefore, PCs have good development prospects in photocatalytic fields such as photocatalytic hydrogen production, [ 110–113 ] photocatalytic degradation of pollutants, [ 114–119 ] and photocatalytic CO 2 reduction. [ 120–123 ] Table 2 shows the photocatalytic performance of some representative PCs.…”
Section: The Applications Of Pcs In Photocatalysismentioning
confidence: 99%
“…In terms of Rahul's research shown in Figure , the fluorinated titania IOs (Au/F TiO 2 IOs) were synthesized by using PS template and further in situ loading Au with controlling size by photochemical reduction treatment. [ 113 ] It displays fivefold amount of H 2 evolution than that of nanocrystalline (nc) TiO 2 . Moreover, PBG of Au/F TiO 2 IOs could be adjusted in line with the size of the colloidal templates.…”
Section: The Applications Of Pcs In Photocatalysismentioning
confidence: 99%